Surface Modification of Polyacrylonitrile Membrane Through Photochemical Graft Polymerization of Acrylic Acid - Dung, Tran Thi; Thu, Ngo Hong Anh; Quyen, Vu Thi; Phuong, Pham Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: